Deforestation, colonization and utilization of land resources in the Atlantic zone of Costa Rica - Sluys, F.R. van; Wielemaker, W.G.; Wienk, J.F. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
11 fig. 38 ref. Sum. (En). También como: Programme Paper - Atlantic Zone Programme (CATIE-AUW-MAG) no. 14